2013
DOI: 10.5047/eps.2013.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotelluric and temperature monitoring after the 2011 sub-Plinian eruptions of Shinmoe-dake volcano

Abstract: Three sub-Plinian eruptions took place on 26-27 January 2011 at Shinmoe-dake volcano in the Kirishima volcanic group, Japan. During this event, GPS and tiltmeters detected syn-eruptive ground subsidence approximately 7 km to the WNW of the volcano. Starting in March 2011, we conducted broad-band magnetotelluric (MT) measurements at a site located 5 km NNW of the volcano, beneath which the Shinmoe-dake magma plumbing system may exist. In addition, temperature monitoring of fumaroles and hot-springs near the MT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Taking into account that the erupted volume of magma is on the order of 0.01 km 3 , we assume that the resistivity structure has not significantly changed since those observations were made. Although the measurement sites in 2010 and 2011 do not overlap with the previous sites, the continuous MT observation at Iwo‐Yama since May 2011 suggested that a resistivity change occurred only at a shallow level (less than several hundred meters) and its amplitude was subtle less than ±10% [ Aizawa et al ., ].…”
Section: Mt Observationsmentioning
confidence: 99%
“…Taking into account that the erupted volume of magma is on the order of 0.01 km 3 , we assume that the resistivity structure has not significantly changed since those observations were made. Although the measurement sites in 2010 and 2011 do not overlap with the previous sites, the continuous MT observation at Iwo‐Yama since May 2011 suggested that a resistivity change occurred only at a shallow level (less than several hundred meters) and its amplitude was subtle less than ±10% [ Aizawa et al ., ].…”
Section: Mt Observationsmentioning
confidence: 99%
“…The accumulation of upwelling volcanic gas beneath this low permeable layer can lead to an increase in temperature and pressure that can potentially cause hydrothermal eruptions. This low permeable clayey layer is conductive and can be imaged using magnetotelluric (MT) methods (e.g., Ussher et al 2000;Aizawa et al 2013). The fact that gases are not as conductive as fluids or clays means that these low permeable clayey caps are often underlain by slightly resistive regions.…”
Section: Introductionmentioning
confidence: 99%
“…After data collection, the binary time series data were converted to text format time series data with physical units (mV/km and nT) using the frequency responses of induction coils and data loggers, and the dipole length of the electric field. Because the time series data were affected by cultural noise from a 60 Hz power line, we performed notch filtering to eliminate 60 Hz noise and its associated odd-order overtones (Aizawa et al 2013). Next, we calculated the MT response function over a 0.003-3276.8-s period range using a bounded influence remote reference code (Chave and Thomson 2004).…”
Section: Data Processingmentioning
confidence: 99%
“…To obtain unbiased impedance, remote reference processing was performed by canceling incoherent noise between an observation site and a reference site (Gamble et al 1979). As a reference magnetic site, we used data from the MT monitoring station at Iwo-Yama, located in the Kirishima Volcanic Complex (Aizawa et al 2013). Although data quality over shorter periods was successfully improved, the data show significant scatter at periods greater than 10 s. By visual inspection, we excluded outliers from the smoothed sounding curve.…”
Section: Data Processingmentioning
confidence: 99%